'Just out of reach': examining the link between subjective wealth, aspirations gaps and empowerment in Central African Republic. (3rd July 2021) - Rougier, Eric; Gondard-Delcroix, Claire; Ballet, Jérôme
ABSTRACT: "What explains the feeling of being disempowered? The literature on aspirations suggests subjectively deprived people may feel disempowered because they consider that any improvement to their lot is simply out of their reach. The present paper provides original and robust evidence that, alongside the well-known objective capabilities related to skills, assets and opportunities, psychological capabilities linked to aspirations also matter. Based on a Central African household survey and tackling endogeneity issues, we show that: (i) feeling subjectively more deprived decreases the probability of reporting a high level of empowerment, defined as power from within, that is the power to change one's life; (ii) the probability of reporting empowerment decreases with the size of the aspirations gap, defined as the negative gap between one's level of subjective wealth and the locality's mean level; (iii) the capability framework is a relevant one to address the complex links between aspirations and empowerment."